Thymic B Cell-Mediated Attack of Thymic Stroma Precedes Type 1 Diabetes Development - Pinto, Ana Isabel; Smith, Jennifer; Kissack, Miriam R.; Hogg, Karen G.; Green, E. Allison (Frontiers in Immunology, 2018)
Type 1 diabetes (T1D) results from a coordinated autoimmune attack of insulin producing beta cells in the pancreas by the innate and adaptive immune systems, beta cell death being predominantly T cell-mediated. In addition to T cells, peripheral B cells are important in T1D progression. The thymus of mice and man also contains B cells, and lately they have been linked to central tolerance of T cells. The role of thymic B cells in T1D is undefined. Here, we show there are abnormalities in the thymic B cell compartment before beta cell destruction and T1D manifestation. Using non-obese diabetic (NOD) mice, we document that preceding T1D development, there is significant accumulation of thymic B cells-partly through in situ development- and the putative formation of ectopic germinal centers. In addition, in NOD mice we quantify thymic plasma cells and observe in situ binding of immunoglobulins to undefined antigens on a proportion of medullary thymic epithelial cells (mTECs). By contrast, no ectopic germinal centers or pronounced intrathymic autoantibodies are detectable in animals not genetically predisposed to developing T1D. Binding of autoantibodies to thymic stroma correlates with apoptosis of mTECs, including insulin-expressing cells. By contrast, apoptosis of mTECs was decreased by 50% in B cell-deficient NOD mice suggesting intrathymic autoantibodies may selectively target certain mTECs for destruction. Furthermore, we observe that these thymic B cell-associated events correlated with an increased prevalence of premature thymic emigration of T cells. Together, our data suggest that the thymus may be a principal autoimmune target in T1D and contributes to disease progression.